FEAR PHENOMENON IN EXISTENTIAL PHILOSOPHY - V. V. Melnyk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. The article describes the fear in the human consciousness as natural and constructive psychological phenomenon indicating an objectless world. The author makes a conclusion as for empirical isolation of the fear determination in the applied psychology and its narrow phenomenological interpretation as well. Person`s attitude to fear is still one of the urgent and key issues in psychoanalytic and philosophical science. Reflection on the fear term and mode is the underlying foundation for existential and metaphysical understanding of the fundamentals of life. Motivational human activity is governed by fear, which concerns new space and time, loneliness, God and transcendent. The feeling of fear is presented in each living being, but in a great extent it is presented in a man with thin mental organization. Purpose. The article analyzes the fear as the integral phenomenon. Methodology. The fear is described as emotion which is important to avoid dangers, so the author used hermeneutical methodology and anthropological integrative approach while doing the research. Originality. The fear is interpreted here as a result of direct physical stimulation of biological reactions within the human body in response to external stimuli (real or imaginary). The fixation of the fact that fear does not inhibit, but rather activates human activities is an important in socio-theosophical interpretations of fear. The author emphasizes that the fear is objectified in the culture and is amenable to the mechanism of minimization. Great attention is paid to the provocation of the depression by fear. The depression is also interpreted as adaptive form of behavior which in its turn allows a weak person to save power and prevent possible conflicts. Conclusions. Thus fear as the modus is considered to be the way of understanding the origin of entity indicating not its substantial meaning but its peculiar «Ontological intensity».